Visual evoked potentials’ responses in hypothyroidism and hyperthyroidism - Gautam, Vikash; Paudel, Bishnu Hari; Lamsal, Madhab; Agrawal, Kopila; Jha, Mukesh Kumar; Maharjan, Sanjay; Thakur, Dilip (International Journal of Research in Medical Sciences, 2019)
Background: Visual Evoked Potentials (VEP) provides important diagnostic and prognostic information regarding the functional integrity of the visual system. This study, describes the effects of less or excess thyroid hormones of adults in visual conduction that helps to know the progression to neurological functional defects. Methods: The study was done in 75 consenting subjects (hypothyroid = 24, hyperthyroid = 25, euthyroid = 26). The VEP parameters N75, P100, N145 latencies and its amplitudes within different thyroid status (hypothyroidism, hyperthyroidism and euthyroidism) were compared. One way ANOVA was used to compare VEP parameters among three groups and Pearson’s correlation to find relation between thyroid hormones and VEP parameters. Results: There was positive correlation of 0.335, 0.338 and 0.301 between amplitudes of N75, P100 and N145 waves and fT3 hormone respectively. Furthermore, fT4 showed a positive correlation of 0.186 and 0.185 with the wave amplitudes of N75 and N145 waves respectively and negative correlation of TSH levels of -0.492, -0.280, -0.397 with amplitudes of N75, P100, N145 waves respectively. Hyperthyroid group had higher in VEP latency than euthyroid group in N75 (73±5.77 vs. 68.54±4.32), P100 (106.42±9.74 vs. 100.94±8.17) and N145 (153.03±16.39 vs. 144.37±7.02) waves. Similarly, hypothyroid group had higher in VEP latency than euthyroid group in N75 (72.12±6.34 vs. 68.54±4.32) wave. Conclusions: Both hypothyroidism and hyperthyroidism led to conduction delay in adults, possibly adversely affecting function of myelin. The prominent visual evoked potential abnormalities in hyperthyroidism and less change in hypothyroidism show that the visual neuropathy is more common in hyperthyroidism.